Innovation in the Service Sector - Stanislav Zaichenko (Foresight and STI Governance)
The services sector is attracting ever more attention of politicians, academics and the business community. This sector is characterized by the fastest growth rate in many countries, it increases innovation performance, provides significant economic growth and has a very prominent part in the employment structure. The article attempts to answer several key questions: • What is the reason for increased attention to services in recent years? • What is the situation with innovations in this sector? • How to establish a national innovation strategy in services? • What specific steps are being taken in this area? • What are the prospects for innovation policy in the services sector?